The Effect of Debt Policies, Profitability, Managerial Ownership Structure, and Liquidity on Dividend Policy - Zainuddin Zainuddin; Okfita Andaresta Mananohas (The Indonesian Journal of Accounting Research, 2020)
This study aims to determine the effect of debt policy, profitability, managerial ownership and liquidity on dividend policy on manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The sample in this study was manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The sampling technique used in this study was purposive sampling, which is the process of taking samples based on certain predetermined criteria. The number of samples in this study amounted to 60 observations. The data analysis technique used is multiple linear regression analysis techniques. The results of this study indicate that 1). Debt policy does not affect dividend policy; 2). Profitability has a positive effect on dividend policy; 3) Managerial ownership has no effect on dividend policy; and 4) Liquidity has no effect on dividend policy. Keywords: Debt policy, profitability, managerial ownership, liquidity and dividend policy